Chapter L’Europa come utopia - Franco, José Eduardo (Firenze University Press, 2023)
Drawing on David Sassoli's inspiring vision, we propose a reflection on Europe as a utopian project with ancient rootedness. This project's uniqueness is marked by its unfinished state, always requiring the impetus of renewed hope. The European Union has to be constantly updating and deepening itself in order to survive. In the conclusion we observe how Europe has been a utopian goal of progress for the countries that comprise it, as is the paradigmatic case of Portugal.